COSINE SIMILARITY FOR ESSAY ANSWER DETECTION - Setiawan, Laurensius Rendi; Nasien, Dewi (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
Saint Mary Senior High School is the one of the famous private schools in Pekanbaru. examination in Saint Mary Senior High School has used a smartphone for multiple choice questions, while in essay questions the pen-and-paper is still used (manual). The number of examination scripts received from students is a problem for a teacher to see the similarity of students' answers with the answer key. At present, there is no system that can assist in checking answers. This study began with the selection stage, which is done by the interview process and filling out the questionnaire. Then proceed with an analysis of this case is used to look for possible development needs of the system. Then the programming language used is PHP and uses MySql database. Web-Based Essay Answer Detection Application Using Cosine Similarity Method in Saint Mary Senior High School. With the application of the essay answer detection application in Saint Mary Senior High School, it is hoped that it will be easier for the teacher to conduct the exam. Besides, it is expected that the application of a computerized system and the use of a database can accelerate the processing of student ranking grades effectively and efficiently.